Investigation of Voltage Rise Rate Effect on the Breakdown Voltage of Solid Insulating Materials Considering Different Electrode Configurations - Akin, Firat; Arikan, Oktay (WILEY, 2025)
For reliable power equipment designs, it is critical to investigate the breakdown performances of insulating materials for a variety of scenarios, including various electrode geometries and voltage characteristics. In this study, the effect of voltage rise rate on the breakdown voltages of presspaper and styrene-butadiene rubber/natural rubber (SBR/NR) is investigated through different electrode geometries. During the experiments, voltages were applied with rise rates of 500 and 3000 V/s, using three different electrode configurations: cylinder-cylinder, sphere-cylinder, and point-cylinder. In order to explain and support the experimental results, a simulation study was performed with COMSOL Multiphysics for electric field analysis.
Keywords: cellulose and other wood products; dielectric properties; rubber; BIPOLAR CHARGE-TRANSPORT; SPACE-CHARGE; DIELECTRIC-BREAKDOWN; STRENGTH; AC; MECHANISM; FIELD; MODEL; RAMP; Polymer Science